HUBUNGAN MINAT BELAJAR SISWA DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN KIMIA DI SMA NEGERI 1 TEBAT KARAI DAN SMA NEGERI 1 KABUPATEN KEPAHIANG - Slamet Rozikin; Hermansyah Amir; Salastri Rohiat (University of Bengkulu, 2018)
[RELATIONSHIP OF STUDENTS LEARNING ACHIEVEMENTS WITH STUDENTS LEARNING INTEREST IN THE CHEMISTRY SUBJECTS AT SMA NEGERI 1 TEBAT KARAI AND SMA NEGERI 1 KEPAHIANG] This study aims to measure the significance of relationships of interest in learning chemistry with the result of chemical learning students in class X IPA residing in SMA Negeri 1 Tebat Karai and a in SMA Negeri 1 Kepahiang at 2016/2017 academic year.. The research is the correlation research. The population in this research is the whole class of X IPA grade in SMAN 1 Tebat Karai and SMAN 1 Kepahiang at 2016/2017 academic year with total population 218 students who at was a total sample of research. Data collection techniques in the study used the instruments form of the interest in learning chemistry. Data analysis tested using correlation analysis, test validity, reliability, linear regression and hypothesis testing. Based on the analysis of the data obtained to the conclusion that there was a significant positive relationship between interest in study with the results of the study chemistry well in SMA Negeri 1 Tebat Karai and SMA Negeri 1 Kepahiang, indicated from the value of F test is greater than F table (30.225 > 3.885) with contributions amounting to 76.4% with the most significant influence indicator is an understanding of the concept of the learning materials with the value of the average correlation of 0,377, 14. From the results of research conducted obtained the conclusion that that interest in learning affects student learning results in class X SMA Negeri 1 Tebat Karai and SMA Negeri 1 Kepahiang.